Material selections in asphalt pavement for wet-freeze climate zones: A review. (20th March 2019) - Chen, Siyu; You, Zhanping; Sharifi, Naser P.; Yao, Hui; Gong, Fangyuan
Highlights: Identification of wet-freeze climate zones in the United States and parts of Canada. Summary of material selections of asphalt pavements in wet-freeze climate zones. Introduction of current practices, and the emerging technologies/materials. Discussion of asphalt binders and up to mixtures related test/design methods. Abstract: The objectives of this review paper are to document current practices in wet-freeze climate zones and introduce emerging technologies that would be largely implemented in wet-freeze climate zones in the near future. A current practice is defined as a procedure that has been shown by research or experience to produce acceptable results and that is established or proposed as a standard suitable for widespread adaptation. An emerging technology is defined as a technique or a material that can improve the asphalt pavement performance, partly replace general materials, and contribute to more sustainable asphalt pavements. This review identified the criteria used to determine locations in the United States and two Canadian provinces with a similar wet-freeze climate. In addition, asphalt binders, asphalt additives/modifiers, asphalt mixture types, reclaimed asphalt mixtures, asphalt mixture test methods, asphalt mixture design methods, and deicers were reviewed. This review concluded with some recommendations in terms of using environmentally friendly materials and selecting cracking and rutting failure criteria to design asphalt mixtures with enhanced performance in wet-freeze climates.